Remaja Masjid melalui Pelatihan Kesenian Hadrah Tradisional dalam Menjaga Warisan Budaya Islam Nusantara di Cipamokolan - Soni Sadono; Didit Endriawan; Donny Trihanondo (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Massive modernization and digitalization currents potentially erode the younger generation's understanding and appreciation of local cultural heritage. This community service activity aims to empower the youth group members of the Al Fitrah Mosque Youth Association or Gemar through traditional hadrah art training in the Cipamokolan area of Bandung City. The implementation method used a participatory mentoring approach encompassing a cross-sectoral coordination preparation phase, a technical training and philosophical value education phase, and a performance showcase phase as an art appreciation space. The results of this activity indicate an increase in the youths' motor and musical skills in playing traditional hadrah instruments. Furthermore, this activity successfully facilitated the process of cultural transmission and intergenerational educational communication when the youths introduced the art form to the women's Islamic study congregation. The conclusion of this community service asserts that restructuring mosque youth activities through religious arts is proven effective in maintaining the existence of Nusantara Islamic culture while safeguarding the social identity of the younger generation from the negative impacts of globalization.